BFGF neutralization stimulates VEGF secretion in melanoma B16 cells. (August 2017) - Wang, Zhiyong; Wei, Pei; Xiang, Junjian; Wang, Hong
Highlights: BFGF neutralization stimulates VEGF secretion in melanoma B16 cells. Upregulation of VEGF provides a survival advantage during bFGF blockade. VEGF inhibition enhances anti-tumor efficacy of anti-bFGF therapy in B16 cells. Abstract: Basic fibroblast growth factor (bFGF), which is expressed by most melanoma cells, can stimulate other growth factors secretion. It is well known that bFGF induces VEGF production; however, the influence of bFGF blockade remains uncertain. Here, we investigated the effect of bFGF neutralization on VEGF expression in B16 melanoma cells. We found that bFGF blockade resulting in increased VEGF expression and activated PI3K/AKT and P44/42 MAPK pathways. Moreover, combined inhibition of bFGF and VEGF led to enhanced activity against B16 tumors in vitro and in vivo. Our dates pointed out that the upregulation of VEGF expression in melanoma tumor cells might provide a survival advantage during bFGF blockade, suggesting its utility as an escape mechanism and as a therapeutic target to heighten anti-bFGF efficacious.